The Motives for Flouting Maxims in Edward Albee’s Who's Afraid of Virginia Woolf? - Efuansyah; Bramantya Pradipta (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the motives for flouting Grice’s conversational maxims in Edward Albee’s Who’s Afraid of Virginia Woolf? focusing on the psychological dynamics among the main characters: George, Martha, Nick, and Honey. This research employs a descriptive qualitative approach, using the play script as the primary data source. The data were collected through close reading and identification of utterances that indicate flouting of the maxims of Quantity, Quality, Relation, and Manner. The data were then analyzed using Grice’s Cooperative Principle and categorized into four types of communicative motives: competitive, convivial, collaborative, and conflictive. The findings reveal a total of 101 instances of maxim flouting. Competitive motives were the most dominant (65 instances), reflecting power struggles and attempts to control conversations, particularly between George and Martha. Conflictive motives followed (33 instances), characterized by the use of false or exaggerated statements to provoke confrontation. Convivial (2 instances) and collaborative (1 instance) motives were less frequent, serving to maintain social harmony and mutual understanding. These findings demonstrate that the flouting of conversational maxims functions as a strategic linguistic tool to express emotional tension, manipulation, and relational conflict. This study contributes to the understanding of pragmatics in literary discourse by highlighting how language is used to reveal psychological complexity and intensify dramatic interaction.